Implicit Religion: Definition and Application - Lord, Karen (Implicit Religion, 2007)
This article provides a foundational definition of implicit religion, using the characteristics identified by the research of Edward Bailey, and examines the applicability of this construct as a research tool in the analysis of religious behaviour. Types of implicit religion and their relationship to concepts such as civil religion, folk religion, invisible religion and wild religion are discussed, demonstrating that the boundaries of religion are not objectively defined. The paper concludes by recommending the construct of implicit religion as a tool to gain a new perspective on the study of religious behaviour.